Inhibition of STING-induced mitochondrial Drp1/N-GSDMD-mediated MtDNA release alleviates Sepsis-induced lung injury - Shishi Zou; Yifan Zuo; Yukai Chen; Tianyu Zhang; Tinglv Fu; Guorui Li; Rui Xiong; Bohao Liu; Yong Hu; Zhaoyu Hu; Chunguang Miao; Xiaojing Wu; et al. (Cellular and Molecular Life Sciences)
Abstract The stimulator of interferon genes (STING) pathway serves as a crucial nexus in inflammatory responses and cell death. Despite its role in Mitochondria-Endoplasmic Reticulum Contact (MERC), the mechanistic contributions to inflammatory outcomes remain poorly understood. In clinical acute respiratory distress syndrome (ARDS) models of COVID-19 infection and animal models of LPS-induced acute lung injury (ALI), the STING pathway is closely associated with the pyroptosis pathway. The macrophage STING-N-GSDMD-mtDNA positive feedback loop, upon LPS challenge, induces inflammatory responses and pyroptosis. The GSDMD inhibitor disulfiram (DSF) specifically abrogates the N-terminal portion of GSDMD anchored to the mitochondrial membrane. Furthermore, macrophage STING mediates the direct interaction between Drp1 and N-GSDMD on mitochondrial membrane by regulating mitochondrial calcium, linking mitochondrial fission to the induction of inflammatory responses. Targeting STING-mediated mitochondrial homeostasis, both genetically and pharmacologically, may play a protective role in preventing and treating sepsis-induced acute lung injury. Overall, our study posits that STING deficiency mitigates the cooperative interaction between N-GSDMD and Drp1 in mediating mitochondrial permeabilization and rupture following LPS challenge, paving the way for further investigations into inflammation and pyroptosis. Graphical abstract